Unclean hand detection machine using vision sensor - Rawaida , Jaafar (2012)
This project is in the collaboration with the Department of Microbiology and Parasitology of Medical campus USM. This project will deliver an automated hand wash screening audit system using a vision system. The amount of the hand wash screening audit is done manually by an expert to monitor the hands under ultraviolet light once it’s been washed. This project is proposed to automate this hand wash screening audit by using a vision system. By using the vision system, the hand wash screening audit will be done automatically and accurately without the attendance of human expert to detect the unclean areas of the hands. The vision system is designed to increase accuracy to detect the unclean areas of washed hands after using the GLO GERM. GLO GERM acts as stimulated germs. This system will not only detect the unclean areas, but will also estimate the percentage of the unclean areas which will be used as further analysis of the efficiency of the system. However, we need to build the hand wash prototype using ultraviolet light and a camera that is connected to the computer to process and display the results of the hand wash screening audit using image processing software. In the image processing technique, we used hand detection to detect the areas of the palm of the hand and stain on palm detection to detect the unclean areas of the hands using HSV thresholding and RGB masking techniques. We detected the areas of unclean hands which dictated by the colored that has GLO GERM stains. The GUI will show the captured image and detected unclean area image and also the percentage of the unclean areas of the hands. The GUI will notify the decision of clean or unclean based on the percentage of unclean areas. This system design is efficient and commercial in the market especially in HUSM for requirements of health care applications. Other hospitals or industries whom hand hygiene is very crucial are potential buyers.